Second Five Year Plan for the Welfare of Backward Classes Government of Vindhya Pradesh - Planning Commission (Planning Commission)
Grants under Article 275 of the Constitution were made available to the state by the government of India in the ministry of home Affairs. For schemes No. 2 and 3 also, special grants were sanctioned by the ministry of Home Affairs, Government India. Scheme No. 4 was financed out if State funds. In so far as financing of schemes is concerned, the II Five Year plan also follows the above pattern.
Backward Classes Welfare Department, Government of Vindhya Pradesh